(untitled) (The Agriculturists, 2010)
An experiment was conducted with a local cultivar of garlic to study the effects of planting date and gibberellic acid on the growth and yield of garlic at the field laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh during November 2001 to April 2002. Early planting influenced the plant height, leaf number, bulb diameter and total dry matter. With the delay in planting time starting from November 7, the yield was chronologically reduced in later plantings. Significantly the highest bulb yield (2.67 t/ha) was recorded when planting was done on November 7 and lowest yield (0.92 t/ha) was obtained from December 22 planted crop. Bulb yield was higher in control plants than those of GA3 treated plants. The interaction effects of planting date and different concentrations of GA3 differed significantly in respect of plant height, number of leaves, bulb diameter and dry weight of roots, leaves and bulbs and yield of garlic.